Child Character from the Psychological Perspective of Islamic Education at MTSN 2 Cirebon - Ratnawati, Etty; Nurhayati, Tati; Nasehudin, Nasehudin (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This research aims to determine the development of children's character from the psychological perspective of Islamic education at MTSN 2 Cirebon because Islamic character is expected to be possessed by students studying at Islamic schools. The method used in this study is a qualitative approach and uses library research. Qualitative research has been happening before the researcher is in the field. Based on this, the authors decided the stages of writing this article were as follows: (1) collecting data, (2) selecting the required data, and (3) analyzing the data so that appropriate conclusions can be reached. The research results collected, selected, and analyzed show that character is a series of motivations, attitudes, behaviors, and skills to do the best. This good character must be supported by knowledge of goodness, the desire to do good, and the ability to do good deeds. Therefore, in developing the factors that influence children's character, starting from a strong family, parental involvement in raising children, parenting patterns applied by parents, consistency, habituation, and exemplary. Apart from that, children need to pay attention to the food they eat. The food factors considered are not only the nutritional and health aspects but also need to pay attention to the halal aspects, both in terms of substances and halal from the method of obtaining them. Character education was chosen to realize the character formation of students or generations of noble people.